Anakinra treatment in patients with refractory inflammatory myopathies and possible predictive response biomarkers: a mechanistic study with 12 months follow-up. Issue 5 (26th April 2013) - Zong, Mei; Dorph, Christina; Dastmalchi, Maryam; Alexanderson, Helene; Pieper, Jennifer; Amoudruz, Petra; Barbasso Helmers, Sevim; Nennesmo, Inger; Malmström, Vivianne; Lundberg, Ingrid E
Abstract : Objective: To perform a mechanistic study on the effect of interleukin (IL)-1 blockade by anakinra in patients with refractory myositis and to explore possible predictive biomarkers. Methods: Fifteen patients with refractory myositis were treated with anakinra for 12 months. Clinical response was assessed by the six-item core set measures of disease activity International Myositis Assessment and Clinical Studies (IMACS) and functional index (FI). Repeated muscle biopsies were investigated for cellular infiltrates, IL-1α, IL-1β, IL-1Ra and major histocompatibility complex-class I by immunohistochemistry. Serum levels of IL-1Ra and granulocyte colony-stimulating factor (G-CSF) were measured by ELISA. T cell phenotype and functional assays were investigated by multicolour flow cytometry. Results: Seven patients had clinical response according to IMACS, four of them also showed improved FI. Responders had higher baseline extramuscular score compared with non-responders. In muscle biopsies, baseline CD163 macrophages and IL-1α expression were inversely correlated with muscle performance after 6 months treatment; all responders had IL-1Ra expression in the post-treatment biopsies but only 3/8 non-responders. In serum, IL-1Ra levels were increased and G-CSF was decreased after 6 months treatment, but their levels and changes were not related to clinical response. For T cells, an inverse correlation between baseline frequency of CD4 activated/memory T cells and decreased creatine kinase levels was observed. Five of six patients demonstrated less IL-17A and more IFN-γ secreting CD4 T cells after 6 months treatment. Moreover, anakinra reduced IL-17A secretion in vitro. Conclusions: Patients with myositis may respond to anakinra. Extramuscular score, muscle CD163 macrophages and IL-1α expression, blood CD4 activated/memory T cells might associate with anakinra treatment response. Blocking the IL-1 receptor disfavoured Th17 cell differentiation both in vivo and in vitro.